Reframing Marital Norms in Indonesian Islamic Law: Nahdlatul Ulama’s Role in Mitigating Patriarchal Practices through Pierre Bourdieu’s Habitus Perspective - Aina Sufya Fuaida; Danu Aris Setiyanto (Journal of Nahdlatul Ulama Studies, 2026)
Patriarchal culture continues to shape family relations among Nahdliyyin communities and is often legitimized through gender-biased religious interpretations. This article examines the role of Nahdlatul Ulama (NU) figures’ exemplary conduct in reducing patriarchal culture through the implementation of equality-based values in the Compilation of Islamic Law (KHI). The study employs a qualitative approach with a case study design and a sociological-juridical perspective. Data were collected through open-ended questionnaires, semi-structured interviews, participatory observation, and documentation, and were analyzed using Pierre Bourdieu’s theory of social agency. The findings indicate that patriarchal reduction is reflected in NU figures’ involvement in domestic work, respect for women, and support for women’s personal development through education and public roles. Their habitus, field, and capital position them as social agents with persuasive cultural influence. This influence fosters a more balanced understanding of KHI principles concerning the rights and obligations of husbands and wives within Nahdliyyin families, thereby contributing to more egalitarian family relations. The study suggests that social transformation in Nahdliyyin families is more effectively achieved through a culturally persuasive approach grounded in uswah hasanah and aligned with the moderating principles of Islam Nusantara. This study provides an empirical contribution by analyzing the application of Aswaja Nahdlatul Ulama values in Islamic family law, advancing theoretical understanding of patriarchal cultural transformation, and proposing a culturally-based intervention model as a reference for both research and practical implementation in traditional Muslim family communities